L’església i els murals romànics de Sant Pau de Fontclara = The Romanesque church and murals of Sant Pau de Fontclara - Paretas, Montserrat Pagès i (Miscel·lània litúrgica catalana, 2023)
This is a study of the damaged Romanesque decoration of the apse of Sant Pau de Fontclara, where the Second Coming or Parousia was depicted in all its splendor, including the Tetramorph and the Elders of the Apocalypse surrounding Christ in Majesty, the Maiestas Domini. The Church of Christ is represented by the apostolic college, presided over by Peter and Paul, whose images also flank two scenes from the life of Saint Paul: his conversion and baptism, on each side of the semi-circular wall of the apse. The windows present the story of Adam and Eve, that of Cain and Abel, and an invocation of the Trinity. The monastery arose in the 9th century within the framework of a wide-ranging political intrigue. The importance of this church is the reason behind its very large apse, which was subsequently decorated, around the year 1200, with the Romanesque mural paintings discussed here.